Private (Rodopi B.V, 2012)
Preliminary Material – Introduction – Letters as Mediators between Private and Public Space /Marita Mathijsen – From the Private to the Public: Some Remarks on Bordalo Pinheiro’s Correspondence in Text and Images /Maria Virgílio Cambraia Lopes – Licensed to Sneak: Why We Should (Be Able to) Read Writers’ Secret Diaries and Letters, and Why Sometimes We Are Not /Bert Van Raemdonck – Written in Prison /Vanda Anastácio – Lithuanian Handwritten Books in the Period of the Ban on the Lithuanian Press (1864–1904) /Mikas Vaicekauskas – Particularly Public and Very Private /Paulius V. Subačius – It is True that They Wrote It /Ángel Rodríguez Gallardo – “Reconstructing Silences”: On the Study and Editing of Private Letters by Spanish Children Evacuated to Russia during the Spanish Civil War /Verónica Sierra Blas – Pessoa’s Notebooks: Windows to Crowded Streets /Jerónimo Pizarro – From Print to Script /Ivo Castro – Hæc Subtilis Ars Inveniendi: Considerations of João Penha’s Literary Archive /Elsa Pereira – The Genetic “I” in Émile Zola /Kelly Basílio – Angelo Colocci’s Crosses and a Text of Airas Carpancho /Rip Cohen – The Secret Life of Ballad Manuscripts /David Atkinson – Daniel Hobbins. Authorship and Publicity Before Print: Jean Gerson and the Transformation of Late Medieval Learning. /Geert Lernout – Ann Hollinshead Hurley and Chanita Goodblatt, editions. Women Editing/Editing Women: Early Modern Women Writers and the New Textualism. /Elizabeth Scott-Baumann – Stephen Hebron. John Keats: A Poet and His Manuscripts. /Sally Bushell – Marilyn Deegan and Kathryn Sutherland. Transferred Illusions: Digital Technology and the Forms of Print. /Dino Buzzetti – Richard Ovenden, Richard Kuhta and Neil Fraistat, editions. Shakespeare Quarto Archive. /John Vincler – John van Wyhe, edition The Complete Work of Charles Darwin Online. /Justin Tonra – Vincent van Gogh: The Letters. Eds. Leo Jansen, Hans Luyten and Nienke Bakker. /Bert Van Raemdonck – Contributors /João Dionísio – Textual Cultures /João Dionísio. Until recently, writings of a private nature have been neglected in literary and textual studies. There are two main reasons for this: the scarcity of pre-modern witnesses of this type of textual production and, in contrast, the over-abundance of material in contemporary writers’ archives. Although in more recent times there has been a marked shift towards the study of private and personal writings, important issues remain to be studied. In the light of genetic criticism and in the context of the broadening attention of textual scholarship to all matters relating to textual production, these texts have acquired a new status, but the legal, philological and historical questions they raise have not been systematically addressed. The new interest of textual scholarship in the processes of creation and dissemination of texts offers an opportunity to reflect more thoroughly on the nature of these documents: on the role they play as witnesses to specific literary or para-literary genres (e.g. letters, diaries), on their significance in circumstances of political repression, and as part of the textual genetic process. This collection of essays includes articles that deal, through heterogeneous approaches, with different aspects of Dutch, English, French, Lithuanian, Portuguese and Spanish written cultures
10.1163/9789401207546
Keywords: Criticism; Textual; Letters; Diaries; Notebooks; Criticism; interpretation; etc